Implementasi Metode Analytical Hierarchy Process (AHP) untuk Analisis Pemilihan Aplikasi Sekuritas Saham Pemula - Nicodias Palasara; Fahmi Heidy Herdiansyah; Feri Prasetyo; Anastasia Siwi; Ahmad Sinnun (Jurusan Informatika Universitas Tanjungpura, 2022)
In the current era of modernization, everything can be accessed very easily via the internet and digitization, this has become a demand for all sectors to be more adaptive in the development of the times, one of which is in terms of the capital market which is now an important part of financial world. Technological progress is a factor that has a very broad effect, there are many conveniences that can be obtained for potential investors, issuers and prospective issuers to get updated information from the capital market. The digitization process does not only affect trading patterns in the capital market, but in terms of business and products in a company that is produced. The selection of stock securities applications includes application design, application ease, application features, and application speed. This is very important because it affects when we make transactions in the capital market to avoid things that are not desirable. The method used is the Analytical Hierarchy Process method with application design criteria, application ease, application features, and application speed. From the results of processing stock security application selection data using Microsoft Excel 2010 and Expert Choice 11 software, the results show that the first rank is IPOT with a value of 0.570 or 57%, then POEMS with a value of 0.217 or 21.7% and finally AJAIB with a value of 0.214 or 21. ,4%